Joints: interventions from social work and applied anthropology (Revista INTEREDU11, 2024)
This work is the result of an innovative and interdisciplinary educational experience between social work and anthropology. Through the round table “Intertwined views: interventions from social work and applied anthropology” programmed within the framework of Complementary Training Activities convened by the Faculty of Social Sciences (Universitat de València), and aimed at students of the subject of Anthropology Second year of the Social Work Degree of the aforementioned university, the objective was to understand the applicability of the contents learned in this subject during the professional practice of Social Sciences in general, and Social Work in particular. Through the experiential story, dialogue between professionals and students was stimulated in a bidirectional sense, through the exchange of experiences, reflections and questions resulting from the interest that this meeting aroused between different profiles and generations that share a transversal social vocation. This innovative proposal from the higher education field, supported by active methodologies and an applied approach, has allowed us to reflect on the importance of anthropology in the training of social workers in the current global context. The results were very positive, with high participation and appreciation from the students.
Keywords: Anthropology; intercultural education; social work; activity learning; educational innovations